Pembelajaran Indoor dan Pembelajaran Outdoor - Shalahuddin Shalahuddin; Muhammad Roihan; Fiqie Alghifari; Muhammad Alfikri Azzaki; Inggrid Ratu Cendana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the learning process, there are various important aspects that must be considered, especially by teachers as transmitters of knowledge. The success of learning depends heavily on the teacher's ability to manage the classroom to create a safe, comfortable, and enjoyable learning atmosphere. Therefore, teachers need to choose the right learning method so that learning objectives can be achieved effectively. One method that can be used is Outdoor Learning, which is learning outside the classroom that provides opportunities for students to develop talents and creativity more broadly through direct experience in the open air. Management of the learning environment is also a crucial factor in supporting learning success. Several things that need to be considered include understanding the nature and development of student intelligence, getting to know students individually, utilizing student behavior in organizing learning, and developing critical thinking, creativity, and problem-solving skills. In addition, teachers need to create an attractive classroom, utilize the environment as a learning resource, provide constructive feedback, and differentiate between students' physical and mental activities. The learning environment itself consists of indoor and outdoor environments. The indoor environment includes school facilities such as classrooms, libraries, laboratories, and auditoriums. Meanwhile, the outdoor environment includes places outside the school that can be used as learning resources, such as museums, mosques, monuments, and fields. Prospective teachers need to understand the importance of managing the learning environment and understand the various types and benefits of learning environments to support an effective learning process.